Ferrogem therapy of women with chronic hypochromic anemia - A. Sh. Makhmutkhodzhaev; I. D. Yevtushenko (Бюллетень сибирской медицины, 2009)
The results of randomized clinical trial of the effectiveness of biologically active admixture «Ferrogem» therapy the women with moderate chronic anemia has been presented. The «Ferrogem» therapy within a four week resulted in complete relief of anemic syndrome, normalization of red blood quantitative and qualitative indices, restoration of reserves of iron.